Pemenuhan Hak Asasi Manusia kepada Etnis Rohingya di Myanmar - Dewa Gede Sudika Mangku (Faculty of Law Hang Tuah University, 2021)
The occurrence of human rights violations against the Rohingya ethnicity in Myanmar has become an international concern. The Rohingya, who have lived for generations in this part of Myanmar, are not getting justice from the Myanmar government. The various human rights violations that have occurred are of course against the basic instruments of international law. This study aims to describe and analyze international human rights arrangements with regard to the protection of the Rohingya ethnicity, as well as any obstacles in providing protection for the Rohingya ethnic group so that no solution has been achieved in resolving these human rights violations. In this study, using a normative legal research method with a statutory approach, a case approach and an analysis approach. The type of legal material in this research is secondary data consisting of primary, secondary and non-legal materials. Then processed and analyzed using prescriptive methods. Based on the research results, it is known that legal protection of the Rohingya ethnicity in accordance with international human rights instruments has not been fulfilled because there are various obstacles in resolving the root of the conflict on human rights violations in Myanmar. Some of them are the reluctance of the Myanmar government to resolve cases of Rohingya ethnic human rights violations. In view of the lack of willingness of the Myanmar government to resolve cases of human rights violations, the UN criticized and attempted to carry out humanitarian intervention to resolve gross human rights violations against the Rohingya ethnic group. For this reason, this paper seeks to elaborate on what responsibilities the Myanmar government should provide for protection according to international human rights as well as what obstacles have caused cases of human rights violations against ethnic Rohingya to be resolved.